A análise geográfica dos gastos municipais em saúde - Ribeiro, Eduardo Augusto Werneck [UNESP] (2005)
Researchers, managers and political agents involved with the health need of including and reliable empiric bases to delineate tendencies and to guide the course of the actions and of the reflections on the Brazilian system of health. Such aspirations coincide with the need of evaluating important changes happened in the section of the Health in a period where, among many events, they stand out those directly to get strong of possible alterations in the offer of services and in the new legislation of the section. This search aim to qualify indicators for the studies that have been accomplished on the theme Geography and public expenses in health. It is looked for, with that, not only to update the basic information already lifted up and published, as well as to deepen the knowledge on such subjects as: How much does for exclusion area wear out? . The distribution of the expenses of health on the public expenses with medical aid shows a favorable tendency to the expansion of the basic cares, although a significant portion of the expense increment if it owes at the displacement of the procedures of high complexity and high cost of hospitals for basics services, not evidencing a significant increase in investment and in costing for the section, causing like this a false investment aspect and reversion of the excluding conditions of most of the population that it is assisted by SUS. What would like to propose is a geographical reading. The distortions and lacks in SUS still persist in the levels more compounds of attendance. The recognition of categories of geographical analysis (under qualitative aspects) as one of the elements builders in the relationship built space and society, expressed in the relationship between the population and the group of the system of health allows to move forward in the understanding of the several action plans in an one plot, in the which the own geography is just a dimension.